Ensuring Privacy in Wireless Channels with Physical Layer Security: A Survey of Encryption Strategies - Revathi, S.; Abisri, M; Aparna, C.; Lidhuna, G. (Journal of Ubiquitous Computing and Communication Technologies, 2024)
This paper reviews various encryption strategies designed to enhance privacy in wireless communication, with a focus on leveraging physical layer security. Exploring techniques that utilize inherent wireless channel features for secure communication, the survey presents the strengths and challenges of each method. The aim is to provide a straightforward overview for researchers, practitioners, and decision-makers, about the evolving landscape of encryption methods in wireless channels for improved privacy. Furthermore, it discusses how these physical layer key generation techniques can be integrated with advanced technologies by providing a suggested model by combining the Machine learning and the Multi authority ciphertext-policy attribute-based encryption (CP-ABE) to ensure privacy in wireless channels.